2019
DOI: 10.1111/evj.13085
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vatinoxan on cardiorespiratory function and gastrointestinal motility during constant‐rate medetomidine infusion in standing horses

Abstract: Summary Background Medetomidine suppresses cardiovascular function and reduces gastrointestinal motility in horses mainly through peripheral α2‐adrenoceptors. Vatinoxan, a peripheral α2‐antagonist, has been shown experimentally to alleviate the adverse effects of some α2‐agonists in horses. However, vatinoxan has not been investigated during constant‐rate infusion (CRI) of medetomidine in standing horses. Objectives To evaluate effects of vatinoxan on cardiovascular function, gastrointestinal motility and on s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 27 publications
(65 reference statements)
0
7
0
Order By: Relevance
“…Administration of medetomidine triggered sinoatrial and second-degree atrioventricular blocks. The administration of α-2 adrenergic receptor agonists cause an initial increase in systemic vascular resistance, producing hypertension and a baroreceptor-mediated reflex bradycardia, followed by a centrally mediated hypotension [34][35][36]. In our study, no difference in MAP and CI was observed in any of the procedures.…”
Section: Discussionmentioning
confidence: 51%
“…Administration of medetomidine triggered sinoatrial and second-degree atrioventricular blocks. The administration of α-2 adrenergic receptor agonists cause an initial increase in systemic vascular resistance, producing hypertension and a baroreceptor-mediated reflex bradycardia, followed by a centrally mediated hypotension [34][35][36]. In our study, no difference in MAP and CI was observed in any of the procedures.…”
Section: Discussionmentioning
confidence: 51%
“…As dobutamine CRI was not discontinued before measurements of CI, it is nearly impossible to distinguish between the effects of vatinoxan and dobutamine, respectively (Pakkanen et al, 2015; Tapio, Raekallio, Mykkänen, Al‐Ramahi, et al, 2019). Nevertheless, in sedated horses co‐administration of vatinoxan to medetomidine significantly increased CI and decreased SVR ten minutes after application (Tapio, Raekallio, Mykkänen, Männikkö, et al, 2019). The MAP in our study was similarly sustained in both groups due to the fact that MAP in group VAT was maintained in physiological limits by starting a dobutamine CRI.…”
Section: Discussionmentioning
confidence: 99%
“…Tapio, Raekallio, Mykkänen, Al‐Ramahi, et al, (2019) used vatinoxan (140 µg kg −1 IV) as a bolus and a similar alpha‐2 adrenoceptor agonist drug dose compared to our study, assuming that 7 µg kg −1 IV medetomidine equals 3.5 µg kg −1 IV dexmedetomidine, observing a marked hypotension after anaesthesia induction in vatinoxan treated horses. The same dose combination was investigated in standing horses, where medetomidine induced cardiovascular changes (bradycardia, increased systemic vascular resistance) could be alleviated by vatinoxan, indicating that inhalational anaesthetics will exacerbate vasodilation leading to hypotension (Tapio, Raekallio, Mykkänen, Männikkö, et al, 2019). However, the comparability to this study is limited as vatinoxan was not given as CRI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise in horses, MK-467 averts the cardiovascular alterations commonly observed with romifidine and detomidine, when administered in combination, without affecting the sedation quality (de Vries et al, 2016;Vainionpaa et al, 2013;Tapio et al, 2018;Pakkanen et al, 2015). A study conducted by Tapio et al (2019) evaluated the effect of vatinoxan on cardiovascular function, gastrointestinal motility and on sedation level during CRI of medetomidine in standing horses. During this study, six healthy horses were given medetomidine hydrochloride, at the rate of 7 µg/kg IV without vatinoxan hydrochloride and at the rate of 140 µg/kg IV with vatinoxan hydrochloride, followed by CRI of medetomidine at 3.5 µg/kg/h for 60 min and they recorded the cardiorespiratory variables and borborygmi and sedation levels were also scored for 120 min.…”
Section: Effects Of Mk-467 In Different Animal Speciesmentioning
confidence: 99%